The Effectiveness of Elsa Speaking Application for Enhancing Pronunciation in English Language Learners - Fauzi, Muhammad; Purnomo, Ryan (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
The integration of technology has become a crucial component in language learning. It enables educators to conduct more engaging and efficient language instruction. Consequently, this study examines the effectiveness of the ELSA (English Language Speech Assistant) Speaking application in enhancing English pronunciation among junior high school students. The data were collected by using tests including pretest and posttest, and then they were analyzed quantitatively, this study using group pretest posttest design. Based on the result of tests, it was found that the value of significance is -4.159 less than the significance level that has been set (α = 0.05). in level of sigificant 005. It indicates that Ho was refused and Ha was accepted which means Elsa application is effective in improving students’ pronunciation. It is evident that ELSA Speak made it easier and more through for the students to pronounce a variety of words. Additionally, the app's capabilities, such as its real-time feedback feature, helped the students pronounce words correctly. Indeed, ELSA Speak can effectively and efficiently help students with their pronunciation. In fact, it can encourage studetns to practice pronouncing words correctly. Therefore, to enrich the literature on teaching English, the researcher recommend that English teachers utilize various applications to enhance students’ proficiency in English.